REORIENTATION STRATEGY OF RELIGIOUS FORUM FROM TRUTH RIVALRY TO KINDNESS RIVALRY IN THE PANDEMIC ERA - Moch. Sony Fauzi; Erna Herawati; Hairul Dharma Widagdo (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2022)
Exclusivism has left a dark history. Heterogeneous life, mutual suspicion, and fighting over adherents became genealogical roots and the forerunner of the seeds of religious exclusivism. This background of conditions has resulted in the potential for religious exclusivism to start infecting Christians and Muslims in the multicultural base on the outskirts of Malang Regency. However, due to the Covid-19 pandemic, the scene on the multicultural floor of Malang Regency, which has been spitting on the narrative of the rivalry of truth, has metamorphosed into a feud of goodness. Then, the method used by the researcher is included in field research and uses a phenomenological perspective. The results of this study, namely the pandemic situation, forced religious patterns to change. In this context, the sacred forum in Malang Regency reorients the rivalry of truth with various things, such as emphasizing tolerance, religious moderation, and considering the Covid-19 pandemic to be a common enemy, so that there is value for unity.